Analysis of blood donor deferrals characteristics in a teaching hospital of south India - Dr. Zubair Hasan; Dr. Seema HS (Tropical Journal of Pathology and Microbiology, 2017)
Context: The health industry today, faces the challenge of safe blood donation. This can be achieved by obtaining blood from voluntary non-remunerated blood donors (VNRD). The rate of deferral has differed from region to region and sometimes in the same region and one centre to another.Aims: 1) To ascertain the chief reasons for blood donation deferral among the blood donors. 2) To study the donor deferral rate and its relation with age and gender.Settings and Design: Descriptive study. Methods and Material: A retrospective study was conducted involving both voluntary and replacement donors who have donated blood to our centre from June 2013 to May 2016.Each donor was selected by a medical officer based on detailed medical history and brief physical examination. Deferral reasons were analysed amongst different categories viz. Gender based (male-female) and various age group categories. Statistical analysis used: Chi square test with significance limit set at 0.05.Results: The total number of donors accepted for blood donation were 1157, out of which 721 were Voluntary donors (62.7%) and 436 were replacement donors (37.3%). Of the total donors who were willing for blood donation, 81 (6.5%) donors were deferred. The donor deferral rate was significantly higher for those above 40 years. Temporary deferrals were commoner among which anaemia was a leading cause. Among permanent deferrals hypertension and jaundice (due to Hepatitis B and Hepatitis C infection) were the common causes.Conclusions: Donor deferral leads to loss of many people from the donation pool to ensure the safety of blood for recipients. Education, motivation, and treatment of these deferred donors due to anemia or other temporary deferrals are important aspects in blood banking, so that these donors may be recruited again.